Biomedical Response to Neisseria gonorrhoeae and Other Sexually Transmitted Infections in the US Military. (28th November 2019) - Garges, Eric; Early, June; Waggoner, Sandra; Rahman, Nazia; Golden, Dana; Agan, Brian; Jerse, Ann
ABSTRACT: Introduction: Sexually transmitted infections (STIs) continue to plague militaries and defense forces. While the historical recognition of the impact of STIs on operations is evident, contemporary surveillance and research activities are limited. As Neisseria gonorrhoeae and other sexually transmitted pathogens become increasingly resistant to antibiotics, the role of the Department of Defense (DoD) in disease surveillance and clinical research is essential to military Force Health Protection. Methods: The Infectious Disease Clinical Research Program (IDCRP) of the Uniformed Services University of the Health Sciences partnered with the DoD Global Emerging Infections Surveillance (GEIS) program to monitor the distribution of gonorrhea antimicrobial resistance (AMR) both domestically and abroad. The DoD gonococcal reference laboratory and repository was established in 2011 as a resource for confirmatory testing and advanced characterization of isolates collected from sites across the continental United States (CONUS) and GEIS-funded sites outside the continental United States (OCONUS). The IDCRP is currently implementing surveillance efforts at CONUS military clinics, including Madigan Army Medical Center, Naval Medical Center Camp Lejeune, Naval Medical Center Portsmouth, Naval Medical Center San Diego, and San Antonio Military Medical Center (efforts were also previously at Womack Army Medical Center). The reference laboratory and repository receives specimens from OCONUS collaborators, including Armed Forces Research Institute of Medical Sciences (AFRIMS; Bangkok, Thailand), Naval Medical Research Unit No. 3 (NAMRU-3), Ghana Detachment (Accra, Ghana), Naval Medical Research Unit No. 6 (NAMRU-6; Lima, Peru), U.S. Army Medical Research Unit – Georgia (USAMRD-G; Tbilisi, Republic of Georgia), and U.S. Army Medical Research Directorate – Kenya (USAMRD-K; Nairobi, Kenya). The gonococcal surveillance program, to include findings, as well as associated clinical research efforts are described. Results: Among N. gonorrhoeae isolates tested within the United States, 8% were resistant to tetracycline, 2% were resistant to penicillin, and 30% were resistant to ciprofloxacin. To date, only one of the 61 isolates has demonstrated some resistance (MIC=1 μg/ml) to azithromycin. No resistance to cephalosporins has been detected; however, reduced susceptibility (MIC=0.06–0.125 μg/ml) has been observed in 13% of isolates. Resistance is commonly observed in N. gonorrhoeae isolates submitted from OCONUS clinical sites, particularly with respect to tetracycline, penicillin, and ciprofloxacin. While no azithromycin-resistant isolates have been identified from OCONUS sites, reduced susceptibility (MIC=0.125–0.5 μg/ml) to azithromycin was observed in 23% of isolates. Conclusion: Continued monitoring of circulating resistance patterns on a global scale is critical for ensuring appropriate treatments are prescribed for service members that may be infected in the U.S. or while deployed. Domestic surveillance for gonococcal AMR within the Military Health System has indicated that resistance patterns, while variable, are not dramatically different from what is seen in U.S. civilian data. Global patterns of gonococcal AMR have been described through the establishment of a central DoD gonococcal reference laboratory and repository. This repository of global isolates provides a platform for further research and development into biomedical countermeasures against gonococcal infections.